2015
DOI: 10.1021/acsami.5b07391
|View full text |Cite
|
Sign up to set email alerts
|

3D Atomic Arrangement at Functional Interfaces Inside Nanoparticles by Resonant High-Energy X-ray Diffraction

Abstract: With current science and technology moving rapidly into smaller scales, nanometer-sized materials, often referred to as NPs, are produced in increasing numbers and explored for numerous useful applications. Evidence is mounting, however, that useful properties of NPs can be improved further and even new NP functionality achieved by not only controlling the NP size and shape but also interfacing chemically or structurally distinct entities into single, so-called "composite" NPs. A typical example is core-shell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Over the past few decades, synchrotron radiation based highenergy X-ray diffraction (HEXRD) coupled to atomic pair distribution function (PDF) analysis has emerged as an important tool to reveal the 3D atomic arrangement of unsupported or supported metal nanoparticles, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] which have a pronounced effect on their structure and shape as well as on their functionality in applications such as catalysis. For example, Petkov and co-workers reported the 3D atomic structure of nanosized Ru [18][19][20] and Au [21][22][23] and binary alloy [24][25][26] particles, indicating that these nanoparticles less than 10 nm in diameter could be considered as nonperiodic, dense packing of metallic atoms that shows characteristic of the fcc lattice with some surface atomic disorder. Here it may be noted that atoms at the nanoparticle surfaces have incomplete coordination spheres, experience signicant surface relaxation and surface environment effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, synchrotron radiation based highenergy X-ray diffraction (HEXRD) coupled to atomic pair distribution function (PDF) analysis has emerged as an important tool to reveal the 3D atomic arrangement of unsupported or supported metal nanoparticles, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] which have a pronounced effect on their structure and shape as well as on their functionality in applications such as catalysis. For example, Petkov and co-workers reported the 3D atomic structure of nanosized Ru [18][19][20] and Au [21][22][23] and binary alloy [24][25][26] particles, indicating that these nanoparticles less than 10 nm in diameter could be considered as nonperiodic, dense packing of metallic atoms that shows characteristic of the fcc lattice with some surface atomic disorder. Here it may be noted that atoms at the nanoparticle surfaces have incomplete coordination spheres, experience signicant surface relaxation and surface environment effects.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 RMC simulations are an established and ideal technique for modeling structure functions of highly disordered materials that requires no crystallographic information. [18][19][20][21][22][23][24][25][26][38][39][40] Coordination number (CN) and bond angle distributions are calculated from the RMC-generated congurations as well, further showing a disordered crystalline structure in detail. Recently, we have reported the 3D atomic structures of Ru nanoparticles in several diameters by means of HEXRD techniques with the aid of RMC simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Both Bragg and diffuse features are collected in the Fourier transform, thus allowing for the structural analysis of materials with limited long-range order and intrinsic structural perturbation, such as those in doped nanocrystal systems . The atomic PDFs can further allow for noncrystallographic nanoparticle model construction to directly observe structural motifs of potential interest. …”
mentioning
confidence: 99%
“…At the same time, several studies have specifically indicated or addressed the presence of interphase correlations in PDF data [e.g. core-shell architectures (Petkov et al, 2015), nanoscale aggregates in bulk oxides (Proffen & Page, 2004) and surface interactions (Page et al, 2011;Chupas et al, 2011;Zhu et al, 2013)]. However, we are not aware of any systematic investigations that directly explore the utility of the PDF's sensitivity to interphase correlations, or exploit its use in tracking aggregation and growth processes.…”
Section: Detecting Phase Aggregation and Growth With Catsmentioning
confidence: 96%